A Method Model Presentation: Online Clinical Mentoring for Physical Therapists Experiencing Professional Isolation. Issue 4 (27th December 2020) - Westervelt, Karen C.; Kunker, Katrina; Patel, Radha; Smith, Elizabeth; Wolitzer, Kaylee
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background and Purpose: Clinical mentoring is essential for the professional development of physical therapists (PTs) and improves confidence and clinical decision making. Physical therapists working in professionally isolated settings with the lack of contact with professional peers face unique challenges, including lack of access to mentors, which can result in diminished job satisfaction, recruitment, and retention. The innovative use of technology, including videoconferencing, can help address the challenges faced by these health care providers by improving access to clinical mentoring. The purpose of this study was to examine the effects of an online model of clinical mentoring on PTs experiencing professional isolation in an outpatient musculoskeletal setting. Method/Model Description and Evaluation: Eight professionally isolated and 4 expert PTs were divided into 4 groups. Three 1-hour online case-based mentoring video sessions were held over the course of 5 weeks. Data were collected from pre and postparticipation surveys and postparticipation focus groups. A mixed-methods analysis was used to evaluate data. Outcomes: Qualitative results for the mentee group revealed 4 themes: perspective, reflection, perceived clinical benefits, and feasibility. Three themes emerged for the mentor group: accessible model, advancing the profession, and perspective. Quantitative analysis revealed significant improvement in 4 areas of confidence. All participants felt that the intervention supported professional attributes; 75% of participants reported the group size as ideal, and 75% of mentees felt that the program improved both confidence and clinical decision-making skills. Discussion and Conclusion: Online clinical mentoring can address several of the barriers faced by PTs who work in professional isolation and allows PTs who would not otherwise have access to postprofessional education to access a mentor remotely.